2016
DOI: 10.3233/bmr-150638
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neuromuscular electrical stimulation at different frequencies on the activations of deep abdominal stabilizing muscles

Abstract: Our results indicate that NMES can preferentially stimulate contractions in deep abdominal stabilizing muscles. Most importantly, 50 Hz NMES produced greater muscle thickness increases than 20 or 80 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, no changes were seen in the thickness of the abdominal musculature according to the dominant or non-dominant side or in the muscle response to EMS as a function of abdominal crease thickness. Other studies in healthy individuals also did not observe differences in thickness in abdominal musculature on both sides, both at rest and during muscle contraction [ 14 , 21 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, no changes were seen in the thickness of the abdominal musculature according to the dominant or non-dominant side or in the muscle response to EMS as a function of abdominal crease thickness. Other studies in healthy individuals also did not observe differences in thickness in abdominal musculature on both sides, both at rest and during muscle contraction [ 14 , 21 ].…”
Section: Discussionmentioning
confidence: 82%
“…Rehabilitative Ultrasound Imaging (RUSI) is a non-invasive, objective, and validated technique to evaluate structural muscle changes and their behavior [ 15 ]. It has high reliability in the measurement of trunk muscles [ 16 , 17 ] and has been used in various investigations on the effects of EMS on the abdominal musculature [ 15 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…NMES has been reported for many years to reeducate and strengthen skeletal muscles [7][8][9] . Cho et al 10) indicated that NMES by low-frequency rectangular pulsed current (LFRP) can stimulate contractions in deep abdominal stabilizing muscles. Most importantly, when analyzing with imaging ultrasonography, it was noted that 50 Hz LFRP produced greater increases in muscle thickness than 20 or 80 Hz LFRP.…”
Section: Introductionmentioning
confidence: 99%
“…EMS has been applied for muscle strengthening, facilitation of muscle contraction and motor control, and maintenance of muscle size and strength during prolonged immobilization in many rehabilitation settings. [1][2][3][4] In addition, EMS programs have been used to improve muscle strength in healthy individuals, and muscle performance in athletes. [5][6][7][8][9][10] Neuromuscular adaptations resulting from EMS training in both healthy and diseased muscles can be as large as, but are rarely greater than, those resulting from voluntary contractions (VCs).…”
mentioning
confidence: 99%